Synthetic Studies toward the Myrioneuron Alkaloids - Aquilina, Jake M.; Smith, Myles W. (Synthesis, 2023)
The Myrioneuron alkaloids are a relatively small family of plant-derived alkaloids that present an intriguing array of structural intricacy and biological properties. As such, these natural products have drawn interest from the synthetic community, resulting in creative total syntheses of several family members. This review showcases recent synthetic efforts towards these polycyclic alkaloids.1 Introduction1.1 Biological Activity1.2 Proposed Biosynthesis2 Synthetic Studies toward the Myrioneuron Alkaloids2.1 Total Synthesis of Myrioxazines A and B2.2 Total Synthesis of Myrionine, Myrionidine, and Schoberine2.3 Total Synthesis of Myrifabrals A and B2.4 Total Synthesis of Myrioneurinol3 Conclusions and Outlook
Keywords: alkaloids; total synthesis; Myrioneuron; asymmetric synthesis; biosynthesis